1994
DOI: 10.1007/bf02087561
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbonic anhydrase in basal and stimulated bicarbonate secretion by the guinea pig duodenum

Abstract: The role of carbonic anhydrase in the process of proximal duodenal mucosal bicarbonate secretion was investigated in the guinea pig. In a series of experiments in vivo, the duodenum was perfused with 24 mmol/liter NaHCO3 solution (+ NaCl for isotonicity) to ensure that active duodenal HCO3- secretion against a concentration gradient was measured. Acetazolamide (80 mg/kg) was infused intravenously to examine the role of carbonic anhydrase on basal and agonist-stimulated HCO3- secretion. Acetazolamide abolished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Early studies applied carbonic anhydrase inhibitors luminally or systemically and found that these maneuvers reduced stimulation of DBS (7,8). The obvious, but as it now turns out incorrect or insufficient, interpretation of these results was that carbonic anhydrase is needed to convert CO 2 , entering the cells from the blood, into HCO 3 Ϫ , destined for secretion, and H ϩ , destined for basolateral export.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies applied carbonic anhydrase inhibitors luminally or systemically and found that these maneuvers reduced stimulation of DBS (7,8). The obvious, but as it now turns out incorrect or insufficient, interpretation of these results was that carbonic anhydrase is needed to convert CO 2 , entering the cells from the blood, into HCO 3 Ϫ , destined for secretion, and H ϩ , destined for basolateral export.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of CO 2 from luminal acid has been suggested to depend on the action of extracellular carbonic anhydrases (5,6). Because CA inhibitors suppressed duodenal HCO 3 Ϫ secretion, CO 2 entry and hydration in the enterocyte was thought to be a major supply pathway for basal and stimulated duodenal HCO 3 Ϫ secretion (7,8), although this issue has remained controversial (9, 10).…”
mentioning
confidence: 99%
“…stimulated active bicarbonate transport in the duodenum. The low effective concentration ofTPA , calculated to be lQ-10mol/ml body [9] and PGFi,, [5]. For these agonists, inositol phospholipids, Ca2+ and PKC would have to play a role as mediators [10].…”
Section: Discussionmentioning
confidence: 99%
“…Electrical vagal stimulation [4] and the mcholinoceptor agonists, carbachol [5][6][7] and bethanechol [8], stimulate DBS in laboratory animals and man. Prostaglandin F2a (PGF2a) and dibutyryl 3',5'-cyclic guanosine monophosphatate (dBcGMP) are agonists of this secretion [9]. These data challenge a role for protein kinase C (PKC) and intracellular Ca2+ in DBS, as was described in pancreatic bicar bonate secretion [10].…”
Section: Introductionmentioning
confidence: 98%
“…The amiloride-sensitive Na ϩ ͞H ϩ exchanger extrudes protons at both the apical and basolateral membranes. Suppression of CA activity with acetazolamide decreases the basal and stimulated duodenal mucosal HCO 3 Ϫ secretion in humans (12), rabbits (13), and guinea pigs (14). In rats, acetazolamide has been reported to decrease bicarbonate secretion (4), whereas other authors have found no effect (15).…”
mentioning
confidence: 99%